2010
DOI: 10.1007/s12035-010-8158-9
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Signaling in the Hippocampus and Its Relation to Pathogenesis of Depression

Abstract: Zinc is released from glutamatergic (zincergic) neuron terminals in the brain, followed by the increase in Zn²⁺ concentration in the intracellular (cytosol) compartment as well as that in the extracellular compartment. Intracellular Zn²⁺ concentration mainly increases through calcium-permeable channels and serves as Zn²⁺ signal as well as extracellular Zn²⁺ concentration. Hippocampal Zn²⁺ signaling may participate in synaptic plasticity such as long-term potentiation and cognitive function. On the other hand, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
50
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 134 publications
(130 reference statements)
1
50
0
Order By: Relevance
“…After ovariectomy, zinc level in hippocampal synaptosomes is significantly increased 18) but that in serum is lowered. 49) Also in our study, the amount of synaptosomal zinc was significantly increased by estrogen deficiency in OVX rats. Synaptic vesicles abundantly contain zinc, especially in hippocampal mossy fiber terminals.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…After ovariectomy, zinc level in hippocampal synaptosomes is significantly increased 18) but that in serum is lowered. 49) Also in our study, the amount of synaptosomal zinc was significantly increased by estrogen deficiency in OVX rats. Synaptic vesicles abundantly contain zinc, especially in hippocampal mossy fiber terminals.…”
Section: Discussionsupporting
confidence: 66%
“…Vesicular zinc is an important modulator of neurotransmission and is linked to the pathophysiology of depression. 14,15,50) It has been reported that a transient increase in zinc in hippocampal CA1 pyramidal neurons causes reversible memory deficit. 51) Therefore, appropriate zinc level is important for maintenance of normal neural functions.…”
Section: Discussionmentioning
confidence: 99%
“…Mg is widely distributed in plant foods, particularly green leafy vegetables, legumes, nuts, seeds and whole grains. Zn is a cofactor of many enzymes that play a role in brain function (1) and is present in regions of the brain associated with the pathophysiology of mood disorders, including the amygdala, hippocampus and cerebral cortex (2) . Zn modulates neuronal excitability by inhibiting both the GABA (γ-aminobutyric acid) and NMDA (N-methyl-D-aspartate) receptors (3) and has shown antidepressant-like activities in animal models (4)(5)(6) .…”
mentioning
confidence: 99%
“…Chronic CS infusion in control mice phenocopied the LTP impairments observed in SI mice, while infusion of the GRs antagonist RU38486 rescued the LTP impairments induced by SI. Exposure of young rats to tail suspension stress for 30 s significantly increased serum CS and attenuated CA1 LTP in hippocampal slices [20]. This effect was mediated by CS-dependent increase in postsynaptic Zn 2+ signal.…”
mentioning
confidence: 82%